Primary Student Spatial Reasoning Abilities: Progression and Challenges - Hasanah, Uswatun; Putrawangsa, Susilahudin; Purwanta, Edi; Agus Setiawati, Farida; Wahyu Purnomo, Yoppy (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Spatial reasoning is essential for success in mathematics and STEM fields, yet it is often overlooked in primary school curricula. This study investigates the levels and progression of spatial reasoning abilities among primary school students in Indonesia, focusing on mental rotation, spatial orientation, and spatial visualization. A cross-sectional study involving 135 students from Year 2, Year 4, and Year 6 used an adapted Spatial Reasoning Instrument. Results showed below-average spatial reasoning abilities overall, with notable improvement with age: Year 2 students averaged a Spatial Reasoning Test Score (SRTS) of 1.66, Year 4 students 2.02, and Year 6 students 2.68. Challenges were identified in tasks requiring multi-step spatial reasoning, spatial language comprehension, and 2D-3D transformations, particularly among younger students. These findings highlight the need for curriculum enhancements and targeted interventions to develop spatial reasoning skills from an early age, improving academic performance in STEM subjects.